(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2023)
Traditionally it is believed that cow dung has germicidal and insect repellent properties in the Indian Sub Continent. South Indian people have been using the natural cow dung for cleaning, lining and painting the courtyard and house premises. In this modern era, owing to the unavailability of natural cow dung, the people have resorted to using synthetic dye (synthetic cow dung) which is called colloquially as “Manjal Sani Powder” in Tamil. Synthetic cow dung powder(Auramine) - a dye compound, even though legally banned, is till date easily available locally with small shops and vendors. Aim of the present study is to explore the postmortem findings of Synthetic cow dung powder (sani powder) poisoning in Western Tamil Nadu i.e, Coimbatore, the Nilgiris, Tiruppur, Erode and Karur districts, the study being conducted in the Department of Forensic Medicine, Coimbatore Medical College.The following parameters were collected and analyzed: the deceased’s sex and age, Post mortem findings, histopathological and chemical analysis reports.A total number of 224 cases were analyzed. Most of the deceased persons are of age between 31 to 40years in females (38.8%) andbetween 41 to 50years in males (36.6%). Most of the deceased persons were males(78.1%). Postmortem findings of yellow cow dung poisoning were yellowish discoloration of skin. Internal findings noted were tongue yellow coated. All the internal organs were stained yellow.Intense Vigil and Strict Enforcement of regulations for manufacturing and selling of synthetic dyes can significantly reduce the incidence of Synthetic Yellow Cow Dung(Saani) powder poisoning.